Playful Work Design (PWD) and Flow: A Critical Review of Theory, Research Gaps, and Future Directions - Mark, Kasa; Sheilla Lim, Omar Lim; Zaiton, Hassan; Connie, Yii (Human Resource Management Academic Research Society, 2025)
This review investigates the role of Playful Work Design (PWD) and flow in shaping employee engagement, with the aim of providing organizations with insights into how these elements can enhance creativity, productivity, and quality of life. Despite growing interest in employee well-being, there is a lack of integrated studies examining the joint effects of PWD and flow. This study addresses this gap by synthesizing empirical and theoretical literatures from 2010 to 2023, highlighting how the incorporation of play into work can improve motivation, job satisfaction, and organizational performance. Flow, a psychological state of heightened attention, is shown to further enhance productivity and innovation. The review identifies research gaps and suggests future directions, particularly focusing on integrating older adult performance with flow. The discussion emphasizes how employees can use these insights to boost creativity, prevent burnout, improve collaboration, and drive innovation. Practical guidelines are also provided for industry practitioners to implement PWD, supporting longterm employee engagement and fostering high-performance work environments.